2013
DOI: 10.1371/journal.pone.0077118
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Fetuin-A Is a Novel Marker for Diabetic Nephropathy in Type 2 Diabetes Identified by Lectin Microarray

Abstract: We analyzed the urine samples of patients with type 2 diabetes at various stages of diabetic nephropathy by lectin microarray to identify a biomarker to predict the progression of diabetic nephropathy. Japanese patients with type 2 diabetes at various stages of nephropathy were enrolled and we performed lectin microarray analyses (n = 17) and measured urinary excretion of fetuin-A (n = 85). The increased signals of urine samples were observed in Siaα2-6Gal/GalNAc-binding lectins (SNA, SSA, TJA-I) during the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 44 publications
4
35
0
1
Order By: Relevance
“…We performed multiple logistic regression analyses based on backward elimination of data (Chang et al, 2015) and constructed a clinical model that excluded ACR to distinguish DN from the non-DN patients. Since ACR is the primary diagnostic parameter, such model also serves to assess the risk factors of DN with micro- and macroalbumia (Inoue et al, 2013). The final model consisted of age, GFR, and serum parameters (uric acid, albumin, total protein, total glycerides, alanine aminotransferase, total bilirubin, direct bilirubin, blood urea nitrogen, and fasting blood glucose).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed multiple logistic regression analyses based on backward elimination of data (Chang et al, 2015) and constructed a clinical model that excluded ACR to distinguish DN from the non-DN patients. Since ACR is the primary diagnostic parameter, such model also serves to assess the risk factors of DN with micro- and macroalbumia (Inoue et al, 2013). The final model consisted of age, GFR, and serum parameters (uric acid, albumin, total protein, total glycerides, alanine aminotransferase, total bilirubin, direct bilirubin, blood urea nitrogen, and fasting blood glucose).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, tubular markers are also correlated to glycemic control (Pontuch, Jensen, Deckert, Ondrejka, & Mikulecky, 1992; Salem et al, 2002) and diabetic retinopathy (Holm, Nielsen, & Hemmingsen, 1994). Recently, the urine and plasma proteome analyses have led to identification of new markers including haptoglobin, kininogen, and Fetuin-A (Bhensdadia et al, 2013; Inoue et al, 2013; Merchant et al, 2013). However, none of these markers has been incorporated into the clinical setting due to various limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, urinary FetA levels were under the detection limit (data not shown), though in a human study in patients with type 2 diabetes urinary FetA was identified as a new risk factor for renal injury (Inoue et al. ). In this short‐term diabetes model, diabetic mice did not develop kidney pathologies.…”
Section: Discussionmentioning
confidence: 95%
“…Fetuin-A glycoprotein was identified as the prognostic biomarker for DN progression (Table 3). [134] Another study confirmed the positive correlation between Siaα2-6Gal/GalNAc (recognized by SNA lectin) expression levels and DN progression and suggested its application in differentiating DN from nondiabetic renal disease (NDRD). [135] However, Yang et al showed that another glycan, (β-1,4)-linked GlcNAc, recognized by the lectin Datura stramonium agglutinin (DSA), could be a biomarker capable of differentiating DN from NDRD.…”
Section: Other Diseases Biomarker Discoverymentioning
confidence: 90%